2011
DOI: 10.2215/cjn.07160810
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse-coordinated Model of Care versus Usual Care for Stage 3/4 Chronic Kidney Disease in the Community

Abstract: SummaryBackground and objectives It is unclear how to optimally care for chronic kidney disease (CKD). This study compares a new coordinated model to usual care for CKD.Design, setting, participants, & measurements A randomized trial in nephrology clinics and the community included 474 patients with median estimated GFR (eGFR) 42 ml/min per 1.73 m 2 identified by laboratorybased case finding compared care coordinated by a general practitioner (controls) with care by a nursecoordinated team including a nephrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(157 citation statements)
references
References 28 publications
1
153
0
3
Order By: Relevance
“…Participants were largely Caucasian seniors, living independently, and a little over half were women (18). Baseline estimated GFR (eGFR) by MDRD equation (age, sex, and serum creatinine) centered around 42 ml/min per 1.73 m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were largely Caucasian seniors, living independently, and a little over half were women (18). Baseline estimated GFR (eGFR) by MDRD equation (age, sex, and serum creatinine) centered around 42 ml/min per 1.73 m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The methods for the trial and the clinical efficacy have been reported elsewhere (18). In an effort to minimize referral biases, a laboratory-based case finding method was employed as described (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 However, in a randomised trial in which patients were randomly assigned to a nurse-coordinated team in secondary care, or to usual care in general practice, no effect on cardiovascular risk-factor control or on clinical end points was found. 36 The opportunity to ask advice from a nephrologist has been studied in a shared care system in the UK. 17 Patients were treated in primary care that was sustained by continuous feedback from nephrologists on the laboratory and blood pressure results.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%